Adversarial ground target tracking using UAVs with input constraints - Zhu, Senqiang (2013)
This paper deals with the problem of adversarial ground target tracking using Unmanned Aerial Vehicles (UAVs) subject to input constraints. For adversarial ground target tracking, tracking performance and UAV safety are two important considerations during tracking controller design. In this paper, a bang-bang heading rate controller is proposed to achieve circular tracking around the target. Exposure avoidance of the UAV to the target and minimizing the exposure time are studied respectively in terms of the initial state of the UAV. The performance of the proposed controller in both cases is also analyzed. Simulation results demonstrate the effectiveness of the proposed approach.